1994
DOI: 10.1523/jneurosci.14-03-01385.1994
|View full text |Cite
|
Sign up to set email alerts
|

Both N- and C-terminal regions contribute to the assembly and functional expression of homo- and heteromultimeric voltage-gated K+ channels

Abstract: The functional diversity of voltage-gated K+ channels may be partially determined by the mechanisms that permit or limit the assembly of molecularly diverse K+ channel subunits. To determine possible amino acid sequence domains required for subunit assembly and expression, we have constructed 15 N- and C-terminal interstitial or truncation deletion mutations in mKv1.1 (MBK1), a mouse Shaker-like K+ channel. We injected Xenopus oocytes with cRNA encoding each of these mutants and coinjected each mutant cRNA wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
55
0

Year Published

1995
1995
2006
2006

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(60 citation statements)
references
References 24 publications
5
55
0
Order By: Relevance
“…The surface expression level in COS-1 cells was determined by using a whole-cell [ 3 H]NEMagitoxin-binding assay and was similar for both WT and ⌬C mutant channels, although slightly higher for the WT channel (Table 1), consistent with previous results for other Shaker-like K ϩ channels (10,37). The yield of correctly folded truncated Shaker channels after affinity purification was 42% of the total protein, compared with Ϸ30% for the WT channel (17).…”
Section: Resultssupporting
confidence: 85%
See 2 more Smart Citations
“…The surface expression level in COS-1 cells was determined by using a whole-cell [ 3 H]NEMagitoxin-binding assay and was similar for both WT and ⌬C mutant channels, although slightly higher for the WT channel (Table 1), consistent with previous results for other Shaker-like K ϩ channels (10,37). The yield of correctly folded truncated Shaker channels after affinity purification was 42% of the total protein, compared with Ϸ30% for the WT channel (17).…”
Section: Resultssupporting
confidence: 85%
“…It is known that in Shaker-like K ϩ channels, C termini are involved in a variety of processes that range from channel gating (10,11) and voltage sensitivity (4) to the binding of the membrane-associated guanylate kinases (12). They also participate in channel assembly in Kv 2.1 (13,14).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…They contribute to the repolarization of single-action potentials, they modulate action potential duration and frequency, and they maintain the internodal resting potential (29,34,45,46). Juxtaparanodal Kv channels are composed of various heteromultimeric combinations of pore-forming Kv1 ␣ (Kv 1.1, 1.2, 1.4, and 1.6) and the associated cytoplasmic Kv␤2 subunits (42,44,47,48). In the juxtaparanodal region, Kv1.1 and Kv1.2 have been shown to colocalize with, and to interact and͞or cluster with, Caspr2, a member of the neurexin superfamily (49,50).…”
Section: Discussionmentioning
confidence: 99%
“…Recently we and others have identified a conserved molecular domain, the T1 domain, encoded within the cytoplasmic N terminus of the ␣-subunit protein that plays an important role in the assembly of K ϩ channel subunit proteins (5)(6)(7)(8)(9)(10). Our studies have suggested that the T1 domain, translated by itself, can self-assemble (6).…”
mentioning
confidence: 88%